THE INTERCONNECTION BETWEEN THE PROFESSIONAL COMPETENCE OF A FUTURE COMMUNICATIONS OFFICER AND THE DEVELOPMENT OF THEIR CORPORATE CULTURE (Physical Culture and Sport: Scientific Perspective, 2024)
In the context of the full-scale Russian-Ukrainian war, the issue of optimal consolidation of the efforts of the structural units of the Armed Forces of Ukraine has become particularly relevant for the effective fulfilment of assigned tasks. The effectiveness of task execution is only possible based on a unified system of corporate goals, values, and relationships. Within the structure of the Armed Forces of Ukraine, the officer is the direct bearer of these goals, values, and relationships. In modern conditions, officers are required not only to possess knowledge and skills in military affairs but also to demonstrate corporate culture, which, considering traditions, values, and patriotism, enables them to make the right decisions in the context of a military-combat or military-service situation. The aim of the article is to consider corporate culture as a component of the professional competence of future communications officers and to establish the interconnection and interdependence between them.The corporate culture of future officers is examined as an integral, professionally significant quality of cadets' personalities, formed based on the structural components of the military-educational environment, a combination of professional-pedagogical and statutory requirements, and the relationships among participants in the educational process, considering the value-goal dominant. It has been established that the main manifestations of corporate culture in future communications officers include a high level of social cohesion and solidarity among individuals and groups; the necessary level of development of professional, civic, and personal awareness; and an orientation towards solving organisational and professional tasks.It is generalised that, in combat situations, corporate culture as a component of professional competence enables future officers to fully implement measures for preparing and executing service (service-combat or operational-service) tasks based on a comprehensive and objective understanding of the assigned tasks, assessing the situation, developing a plan, making decisions, communicating tasks to subordinates, organising coordination, providing comprehensive support, and exercising management.
Keywords: corporate culture; future communications officers; corporate values; professional competence; preparation